2016
DOI: 10.17795/iji-38260
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Behavior of Mothers about Antibiotic Use in Children Under Six Years Old With Upper Respiratory Tract Infections

Abstract: Background: Upper respiratory tract infections (URTIs) are common in children. The cause of URTIs is usually viral, but parents' attitudes often contribute to inappropriate prescription of antibiotics, promoting antibiotic resistance. Objectives: The objective of this study was to study the knowledge and behavior of mothers about antibiotic use in children under six years old with URTI. Methods: Ninty-seven mothers with children under six years were evaluated in a semi-kap study about antibiotic use in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Therefore, any deviation in the health of children is first recognized by their mothers especially where there are visible signs and symptoms of these diseases or infection. Also, Soleimani, Shahri, Teimouri, Sargolzaei, Ghavampour, [4] reported that the cause of respiratory tract infections especially the upper respiratory tract infections is usually viral but parent's attitudes often contribute to appropriate prescription of antibiotics thereby promoting antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any deviation in the health of children is first recognized by their mothers especially where there are visible signs and symptoms of these diseases or infection. Also, Soleimani, Shahri, Teimouri, Sargolzaei, Ghavampour, [4] reported that the cause of respiratory tract infections especially the upper respiratory tract infections is usually viral but parent's attitudes often contribute to appropriate prescription of antibiotics thereby promoting antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%